Comparação da força e endurance da musculatura respiratória e da capacidade funcional em crianças e adolescentes saudáveis e asmáticas. - Betania Luiza Alexandre (2008)
Comparison of strength and endurance of the respiratory muscles and functional capacity in healthy and asthmatic children INTRODUCTION: Pathophysiological changes from asthma and/or pharmacological therapy can affect the performance of respiratory muscles. However, the effect of this dysfunction on functional capacity is yet to be established. PURPOSE: Assess and compare the strength and endurance of the respiratory muscles and functional capacity in healthy and asthmatic children. METHODS: Ninety-five male and female children (6 to 14 years) considered to be healthy (CTRL-M and CTRL-F) and 100 children diagnosed with asthma (Asthma-M and Asthma-F) participated in the study. The parameters evaluated by spirometry were FVC, FEV1; FEV1/FVC; FEF25-75% and MVV. We evaluated the maximum inspiratory (MIP) and expiratory (MEP) pressure and endurance of muscles inspiratory from 30 and 70% of MIP (Tlim 30% and 70%, respectively). To assess inspiratory muscle endurance, an alternative device was developed which was capable of carrying out pressure measurements above those on the instrument currently available for clinical practice. Functional capacity was assessed by the six-minute walk test (6MWT). Participants performed the 6MWT twice under controlled conditions a 30- minute interval between tests so that cardio-respiratory variables could return to baseline. These variables were systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), respiratory rate (BR) and peripheral saturation (SpO2). The level of dyspnea perception upon effort was measured by the Borg scale administered before and after the tests. Final analysis considered the cardiorespiratory variables corresponding to the test with the greatest distance traveled. The physiological cost index was estimated from the relation between variation in the initial and final HR and average speed achieved on the 6MWT {(HRi-HRf / average speed, bpm/m/s)}. RESULTS: FVC was normal in the control and asthma groups. FEV1, FEV1/FVC, FEF25-75% were significantly lower in the Asthma-M and Asthma-F groups compared to CTRL-M and Control-F groups. MVV was significantly lower in Asthma-F group compared to the other groups. MIP in the Asthma-M group was significantly lower compared to CTRL-M. MEP was significantly lower in the Asthma-M group compared to the CTRL-M and CTRL-F groups. Tlim30% was significantly higher than Tlim70% in all groups evaluated. The Asthma-M and Asthma-F groups exhibited a significant reduction in Tlim30% and Tlim70% in relation to the CTRL-M and CTRL-F groups. There was no difference between the control and asthma groups (both sexes) regarding the distance covered on the 6MWT. There was no significant difference between tests within the different groups, indicating good reliability. There was also strong correlation between the distances covered on the first and second test in the different groups. The physiological cost index was significantly lower in Asthma-M and Asthma- F groups (0.40 ± 0.08 and 0.40 ± 0.07 bpm/m/min) compared to the CTRL-M and CTRL-F groups (0.47 ± 0.13 and 0.50 ± 0.11 bpm/m/min). The initial HR in the Asthma-M (84 ± 10.31 bpm) and Asthma-F (82 ± 7.67 bpm) groups was significantly lower than the CTRL-M (93± 10.79 bpm) and CTRL-F (91± 11.05 bpm) groups. Similar results were seen at the end of the test. The Asthma-M (123 ± 9.71 bpm) and Asthma-F (118 ± 10.22 bpm) groups exhibited a significant reduction in HR in relation to the CTRL-M (140.1 ± 10.50 bpm) and CTRL-F (140.0 ± 9.56 bpm) groups. Initial SBP in the Asthma-M (105.9 ± 11.43 mmHg) and Asthma-F (100.6 ± 8.6 mmHg) groups was significantly higher than the CTRL-M (95.0 ± 6.93 mmHg) and CTRL-F (94.65 ± 8.26 mmHg) groups. There was a significant increase in final SBP in the Asthma-M (117.6 ± 13.48 mmHg) and Asthma-F (111.1 ± 10.36 mmHg) groups compared to the CTRL-M (105.0 ± 7.70 mmHg) and CTRL-F (105.3 ± 8.82 mmHg) groups. The Asthma-M group (16.47 ± 2.01 irpm) exhibited a significantly RR in relation to the CTRL-F group (15.44 ± 0.82 irpm). There was a significant increase in final RR in the Asthma-M group (22.30 ± 1.86 irpm) compared